Customization of an optical probe device and validation of a signal processing procedure to study gas-liquid-solid flows. Application to a three-phase internal-loop Gas-lift Bioreactor - Mota, A. (2015)
The study of local hydrodynamic properties of three-phase bioreactors in biotechnology processes is of great importance, mainly because of the complex interaction between bioreactor and microorganisms. However, classical techniques used for measuring local hydrodynamic properties such as single needle probes are mainly limited to two-phase flows. In this work it was developed and validated a new system, based on the customization of an optical probe initially designed in LEGI. The necessity of a new system was due to the agglomeration of the solid-phase (spent grains which are used as the micro-organisms carrier for the targeted application) around the optical tip, which influences the measurements. This new system allows for the measurement of the main local gas-phase properties in a complex gas-liquid-solid mixture. The new system was first validated for air-water system in an internal loop gas-lift reactor and then applied to a spent grains-air-water mixture at low solid load in an internal gas lift reactor. In addition, experiments using complementary techniques (as high speed camera and PIV) were performed that allowed for the validation of the new system and the explanation of possible physical mechanisms that are underlying on this multiphase system. The system developed has the potential for improvement and use in several biotechnology applications.